2014
DOI: 10.1007/s10865-014-9573-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-drinking and alcohol-related harm in undergraduates: the influence of explicit motives and implicit alcohol identity

Abstract: The present study investigated how pre-drinking could be explained using a model based on dual-systems theory, incorporating measures of explicit and implicit constructs. Undergraduate students (N = 144; 44 male; 100 female; M age = 20.1 years), completed an online survey comprising measures of pre-drinking motives, a measure of pre-drinking cost motives, and an alcohol identity implicit association test. Variance-based structural equation modelling revealed that the predictors explained 34.8% of the variance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…These factors are consistent with research that has identified cost and availability of alcohol as key determinants of excessive alcohol consumption, particularly in young people [43][44][45][46][47]. This is particularly important for policy makers as it seems that participants considered the increasing affordability of alcohol to be the most significant contributor to its growing availability, not extended opening hours.…”
Section: Discussionsupporting
confidence: 83%
“…These factors are consistent with research that has identified cost and availability of alcohol as key determinants of excessive alcohol consumption, particularly in young people [43][44][45][46][47]. This is particularly important for policy makers as it seems that participants considered the increasing affordability of alcohol to be the most significant contributor to its growing availability, not extended opening hours.…”
Section: Discussionsupporting
confidence: 83%
“…Research in the field of non-conscious processes have adopted multiple theoretical paradigms and research methods (e.g., Allom, Mullan, & Hagger, 2016;Houben, Wiers, & Jansen, 2011;Keatley, Clarke, & Hagger, 2012;Perugini, 2005;Presseau et al, 2014), although all have commonalities in their adoption of an overall dualprocess framework. For example, research has focused on the predictive validity of implicit attitudes, beliefs, and motives (Caudwell & Hagger, 2014;Keatley, Clarke, & Hagger, 2013), the effect of health goal and action activation and priming (Fishbach, Friedman, & Kruglanski, 2003;Henderson, Hagger, & Orbell, 2007;Papies, 2016a), and measurement and training of inhibitory control (Allom et al, 2016;.…”
mentioning
confidence: 99%
“…Hagger, Anderson, Kyriakaki, & Darkings, ). Given the reported financial hardship experienced by Australian university students (James, Bexley, Devlin, & Marginson, ) and research indicating that the price of alcohol is an important factor determining university students’ alcohol consumption behaviour (Caudwell & Hagger, ; Miller & Droste, ), it is likely that the cost of drinking or the financial situation of students may be a good example of these barriers. Generally speaking, the significant direct effect of past behaviour on pre‐drinking frequency suggests that substantial variance is unaccounted for by the model variables.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, impulsive systems are characterised by perceptual, cue‐based influences on behaviour (Strack & Deutsch, ). Researchers using measures of implicit motivational constructs, such as the implicit association test and go/no‐go association task, have demonstrated their effectiveness in predicting a range of alcohol consumption outcomes (Caudwell & Hagger, ; Keatley et al., ; Lindgren et al., ; Thush & Wiers, ; Wiers et al., ). Given the weak intention–behaviour relationship observed in the present study and considerable effect of past behaviour, it is worth ascertaining the influence of constructs from the impulsive system in predicting pre‐drinking.…”
Section: Discussionmentioning
confidence: 99%